ON LOCAL LINEAR REGRESSION ESTIMATION IN SAMPLING SURVEYS - Kikech, Conlet B.; Simwa, Richard O.; Pokhariyal, Ganesh P. (Far East Journal of Theoretical Statistics, 2017)
A model based survey is employed to estimate the unknown values of the survey variable, using the local linear regression approach. In particular, a local linear regression estimator in model based surveys is studied. Variance comparisons are made between the derived estimator and the Nadaraya-Watson regression estimator which show that the two estimators are asymptotically equivalently efficient
Keywords: Linear regression; Estimation; Sampling surveys